Networking dalam Kebijakan Optimalisasi Terminal Terpadu Pulo Gebang - Giang Hardiono; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
Pulo Gebang Integrated Bus Station is a real proof that DKI Jakarta Government have commitment to improve the public transportation for people. But in reality it is seen that the use of stakeholder networks by DKI Jakarta Government for the improvement of Pulo Gebang Integrated Bus Station still far from optimal. The problems are : How is the Government's effort in involving stakeholders in optimization policy of Pulo Gebang Integrated Bus Station? How stakeholder roles are involved in optimization policy of Pulo Gebang Integrated Bus Station? The purpose of this study is to explain the efforts of the government in involving stakeholders in the optimization policy of Pulo Gebang Integrated Bus Station and explains the role of stakeholders involved in the optimization policy of Pulo Gebang Integrated Bus Station.The research was conducted using public policy theory, and network management. The method used in this research is qualitative method. Data collection techniques were conducted using interviews with resource persons, written document review, and supporting literature.The result of research shows that the utilization of stakeholder network by DKI Jakarta Government in creating optimal service of Pulo Gebang Integrated Bus Station is not good enough. Although the Jakarta Transportation Department has established the Jakarta City Transportation Council that functions as a miniature community. This is evidenced by complaints from various stakeholders outside the Government who consider the lack of involvement in direct-planning policy. The role of stakeholders is limited on the implementation of a policy issued by the Government. Therefore the Government should be better on utilizing the network to create an optimal service of Pulo Gebang Integrated Bus StationKeyword : Network, Pulo Gebang Integrated Bus Station , Stakeholder.